Pricing of Intermodal Transport. Lessons Learned from RECORDIT - Ricci, Andrea (European Journal of Transport and Infrastructure Research, 2003)
Intermodal transport is defined as a sequence of activities involving modal haulages, transhipments and terminals, and requiring the intervention of a variety of operators, whose roles partially overlap and compete. This entails an inherent complexity of the cost and price formation mechanisms, and an overall lack of transparency resulting both from the technical difficulty to establish a reliable and effective accounting framework, and from the high level of competition currently observed between operators. Specific obstacles to cost valuation and pricing are also related to the choice of the units of measure, whereby intermodal traffic is usually assessed with reference to the Loading Unit concept, rather than in terms of vehicles moved. The RECORDIT project (Real Cost Reduction of Door-to-door Intermodal Transport) is briefly presented, with particular reference to its pricing-relevant objectives: designing an original accounting framework for intermodal transport, and documenting the value of individual cost items (both internal and external) based on the detailed, bottom-up analysis of three intermodal trans-European corridors and their all-road competing alternatives. Intermodal transport is found to be consistently cheaper than all-road solutions, and its external costs significantly lower, thereby confirming the high potential of intermodal transport in increasing the sustainability of the transport sector. Lead times are however substantially longer than for road, which contributes to explain the currently limited market share of intermodal transport services. For price setting purposes, RECORDIT has carried out a comparison between social costs (internal + external) and taxes and charges currently paid. The evidence from the three corridors analysed does not lead to uniform conclusions, owing to a high level of variability of results in relation to corridor-dependent parameters, and thereby confirming the need for a price-setting approach that allows to adequately reflect the specific characteristics of each route. Further research and policy initiatives can be envisaged to facilitate the pricing reform process, particularly directed at reducing information gaps and increasing transparency, also through the establishment of more effective institutional and market mechanisms.